Harlequin Ichtyosis: A Case Report - Yetkin Karasu; Tuyan İlhan; Sinan Karadeniz; Orhan Gelişen (Medical Network, 2009)
Harlequin ichthyosis is a severe and usually fatal congenital keratinization disorder. Although it has many characteristic findings on prenatal ultrasound such as a wide gaping mouth, intrauterine growth retardation, short limbs, joint contractures, edema of the hands and feet and cloudy amniotic fluid, most of the time it is diagnosed at birth. In this case report we summarize a patient who delivered a baby with Harlequin ichthyosis.